Application of Newmark's Theory in the Transfer of the Unit of Culture in the Translation of Arabic Novels - Akram Madani; Javad Asghari (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2021)
Relying on Newmark's theoretical framework, the present study examines the quality of transferring the unit of culture and the performance of translators in translating the novels Miramar, Zaqaq al-Muddaq, and the Nile Trilogy by Najib Mahfouz, The Season of the Hijrah to the North, and Ars al-Zain by al-Tayyib Saleh and Daruz al-Bulgrad by Rabbi to measure the degree of conformity of translation with the components of this theory. After reviewing and adapting the original text and Persian translation based on Newmark theory, it was found that in translating these novels, the methods of transmission, localization, and cultural equivalent have been most used in transmitting the unit of culture. Cases have not been successful in conveying cultural categories. Many cultural categories, including the names of food, clothing, antiquities, institutions and organizations, customs, etc., without explanation in the footnote, are only transferred to the target culture and make it difficult for the reader to understand, which is one of the weaknesses of translators.